1994
DOI: 10.1897/1552-8618(1994)13[517:teoddo]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Diflubenzuron (Dimilin®) on Selected Mayflies (Heptageniidae) and Stoneflies (Peltoperlidae and Pteronarcyidae)

Abstract: Two types of laboratory toxicity tests (exposure in water and feeding) were conducted to determine the effects of diflubenzuron (DFB) on nontarget aquatic insects. The mayflies Cynygmula subaequalis, Sfenacron interpunctatum, Stenonema meririvulanum, and Stenonema femoratum (Heptageniidae) and the stonefly Peltoperla arcuata (Peltoperlidae) were exposed to DFB in water for 96 h, then transferred to pesticide-free water and observed for 36 d. The mayflies were exposed to 0, 0.6, 5.6,55.7, or 557.2 ppb and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…the shredder/collector-gatherers Ephemerella dorothea and Eurylophella funeralis, and Heptageniidae (p ϭ 0.096), the mayfly family that included the scraper/collector-gatherer species Stenonema, Epeorus, and Stenacron. Heptageniid mayflies were shown to be sensitive to DFB concentrations in water of 0.6 ppb in an earlier study in our laboratory [15]. Differences in mean density between streams in treatment and reference watersheds were also observed for oligochaete worms and flatworms (Turbellaria).…”
Section: Invertebrate Responsessupporting
confidence: 56%
See 3 more Smart Citations
“…the shredder/collector-gatherers Ephemerella dorothea and Eurylophella funeralis, and Heptageniidae (p ϭ 0.096), the mayfly family that included the scraper/collector-gatherer species Stenonema, Epeorus, and Stenacron. Heptageniid mayflies were shown to be sensitive to DFB concentrations in water of 0.6 ppb in an earlier study in our laboratory [15]. Differences in mean density between streams in treatment and reference watersheds were also observed for oligochaete worms and flatworms (Turbellaria).…”
Section: Invertebrate Responsessupporting
confidence: 56%
“…Studies by Swift et al [9] and Harrahy et al [15] showed that DFB residues toxic to shredders can remain on leaves in a stream for up to 4 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In insects, chitin synthesis can resume following a limited exposure period (Grosscurt and Jongsma 1987). Effects may be either the result of a steady build-up of the contaminant to a threshold level in the organism over time or there may be a latency period prior to the manifestation of effects (Harrahy et al 1994). In the latter case, we may expect latent effects after a certain period of time even if the organisms were removed from the toxicant.…”
Section: Introductionmentioning
confidence: 99%